Characterisation of delaminated GAFCHROMIC™ EBT3 films in clinical photon, proton and 192Ir brachytherapy source. (June 2019) - Tagiling, N; Ab Rashid, R; Abdullah, R; Dollah, N; Geso, M; Tominaga, T; Akasaka, H; Kie, K; Rahman, WN
Abstract: This paper aims to assess the dose-response characteristics of delaminated GAFCHROMIC™ EBT3 films for radiotherapy beams. Delaminated EBT3 films were produced by peeling off the top polyester substrate of original EBT3 using surgical precision forceps. The films were irradiated to 500 cGy with photon beams of 6 MV and 10 MV, while proton and 192 Ir exposures were conducted at nominal energies of 150 MeV and 0.38 MeV respectively. Digitisations were made using a flatbed scanner in Red-channel for optimum sensitivity. Analyses of data fitting, reading reproducibility, film integrity and energy dependency were then implemented for comparison with original EBT3 films. Results of R 2 in each curve suggested that the selected non-linear function appropriately fits the data with low reduced chi-square. However, the delaminated films experience integrity degradation of up to 13% due to active layer distress, affecting the reading reproducibility with values extending to 1.0%. Plus, the mean relative response ratio of energy dependency for delaminated EBT3 in photon irradiations was observed at 0.97, which is inferior to their original counterpart. In summary, the delaminated EBT3 yields comparable dose-response behaviour despite integrity deterioration. It is important to factor film delamination uncertainties into existing uncertainty budget as it is instrumental in reading dose-response deviations. Accurate evaluation together with reliable fabrication processes could make delaminated EBT3 attractive in specific applications including α-particles dosimetry and ultraviolet radiation monitoring.